Aspirated stop consonants before low vowels, a problem of delimitation - its causes and consequences - Fischer-Jørgensen, Eli; Hutters, Birgit (Annual Report of the Institute of Phonetics University of Copenhagen, 1981)
Attention is drawn to the fact that low vowels may show a gradual start after aspirated consonants, so that it is possible to consider the vowel to start at different points: (a) at voicing start, (b) at the start of Formant 1, (c) at the start of higher formants. The choice of delimitation is shown to have serious consequences for the statement of various temporal relations. It is argued that the choice of point (c) is the most rational choice, both from the point of view of production and perception. It also gives the most regular temporal relations.